A NusG Specialized Paralog That Exhibits Specific, High-Affinity RNA-Binding Activity. Issue 15 (23rd July 2021) - Elghondakly, Amr; Wu, Chih Hao; Klupt, Steven; Goodson, Jonathan; Winkler, Wade C.
Graphical abstract: Highlights: The NusG CTD interacts with other proteins to affect transcription elongation. The NusG paralog LoaP exhibits a novel RNA-binding activity through its CTD. LoaP binds specifically to a small hairpin in the mRNAs that it regulates. The LoaP ribonucleoprotein complex is required for antitermination. This discovery expands the known intermolecular interactions for the NusG CTD. Abstract: Bacterial NusG associates with RNA polymerase (RNAP) through its N-terminal domain, while the C-terminal domain (CTD) forms dynamic interactions with Rho, S10, NusB and NusA to affect transcription elongation. While virtually all bacteria encode for a core NusG, many also synthesize paralogs that transiently bind RNAP to alter expression of targeted genes. Yet, despite the importance of the genes they regulate, most of the subfamilies of NusG paralogs ( e.g., UpxY, TaA, ActX and LoaP) have not been investigated in depth. Herein, we discover that LoaP requires a small RNA hairpin located within the 5′ leader region of its targeted operons. LoaP binds the RNA element with nanomolar affinity and high specificity, in contrast to other NusG proteins, which have not been shown to exhibit RNA-binding activity. These data reveal a sequence feature that can be used to identify LoaP-regulated operons. This discovery also expands the repertoire of macromolecular interactions exhibited by the NusG CTD during transcription elongation to include an RNA ligand.